2023
DOI: 10.3390/jcm12144662
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Pharmacological Protocol with Pentoxifylline and Tocopherol for the Management of Medication-Related Osteonecrosis of the Jaws (MRONJ): A Randomized Study on 202 Osteoporosis Patients

Abstract: Medication-related osteonecrosis of the jaws (MRONJ) is a challenging situation in clinics. Previous studies have shown that pentoxifylline combined with tocopherol proved to be beneficial in patients with osteoradionecrosis, due to their antioxidant and antifibrotic properties. The aim of this randomized study was to evaluate the effect of pentoxifylline and tocopherol in patients that had developed MRONJ after tooth extractions. The study population consisted of 202 Stage I MRONJ female patients with an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Significantly improved healing with a reduced mean time was highlighted after HBO addition to conventional treatment. Recently, Colapinto et al reported that pentoxyphyline and tocopherol improved healing after surgery (Colapinto et al, 2023). Ozone (O 3 ) therapy, applied topically (Agrillo et al, 2012) or infiltrated (Di Fede et al, 2022), has also been suggested in combination with conventional MRONJ treatment and has shown positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly improved healing with a reduced mean time was highlighted after HBO addition to conventional treatment. Recently, Colapinto et al reported that pentoxyphyline and tocopherol improved healing after surgery (Colapinto et al, 2023). Ozone (O 3 ) therapy, applied topically (Agrillo et al, 2012) or infiltrated (Di Fede et al, 2022), has also been suggested in combination with conventional MRONJ treatment and has shown positive results.…”
Section: Discussionmentioning
confidence: 99%